Apuntes iniciales de una búsqueda metodológica para el análisis de procesos de articulación interorganizacionales (2011)
ABSTRACT: This paper is intended to create a short review on the different fields of studies that have considered in a certain way, the organizational articulation as a problem part of their reflections. The objective is to expose some concepts excluded from the communication studies, especially, those referred to inter-organizational articulation and network constructive processes. A review is made through some concepts of economy (cost-benefit relations), political science (power and political behavior), sociology (interaction and communication), psychology (personal networks and affection), organizational theory (interdependency) and social network analysis as a methodology (social structures).